Research of the model of an active four-quadrand transmitter of ac main electric vehicle (Transport systems and technologies, 2019)
The article considers the analysis of the features of the asynchronous traction electric drive of the DS-3 electric locomotive with an active four-quadrant converter when powered by a contact AC network. The calculation of the model parameters was performed and the transient process when switching power keys is studied on the basis of a mathematical description of the processes of the four-quadrant converter.Expressions are given for determining the power factor and phase shift between voltage and current. A simulation model of the four-quadrant converter of the DS-3 electric locomotive has been developed. The relative parameters of the traction transformer are calculated based on the passport data. A study of the model of a four-quadrant converter was carried out, the dependences that were obtained: phase shift between the input voltage and current on the modulation depth and phase shift of the clock signal; output voltage on modulation depth. The values of the phase shift angles were determined during the implementation of traction and regenerative braking modes. The influence of the parameters of the four-quadrant converter on the energy characteristics of the traction converter were analyzed. Measures are proposed to increase the power factor, improve the quality of the current consumed from the contact network and reduce the level of voltage ripple in the DC link.
Keywords: active four-quadrant converter, simulation model, energy characteristics of an electric locomotive